FUNCTIONAL STRUCTURE OF EMOTIONS AS A MENTAL STATE OF PERSONALITY IN THE SYSTEM OF INTERACTION OF TEACHER AND 5 STUDENTS - Saunova, Yu.O. (Pedagogy of Higher and Secondary Education, 2022)
The article is illuminate the problem of the functional structure of emotions at Be system of interaction between the teacher and the pupil. Author singles out and exposes the functions of the person’s emotions al the educational process.